An Advanced Course of English Study - Borisenko, I. I. (Kiev Head Publishing House, 1988)
An Advanced Course of English Study is intended as a working manual and a text-book for senior students of International Relations and International Law Departments who have already achieved a good command of the English language. It comprises 12 units, which make up the bulk of the book and can be covered in two semesters of intensive study, and three appendices. The unit approach makes it possible for each teacher to determine the order of presentation of material best suited to the particular needs of a class.
Keywords: English Practice